BLDS Appliances.Co “MaxiCal 4 in 1 Breakfast Station "/ Nur Liyana Shahira Kamaruzaman - Kamaruzaman, Nur Liyana Shahira (2020)
The name of our business company is BLDS Appliances.Co. Our business type that we generate is partnership which is the partner has limited liability restricted to the percentages of amount capital invested. The profit or loss will incurred by each partner depend on how much amount capital invested by the partners. BLDS Appliances.Co is a partnership company that has been established on 1st December 2018. The company focuses on goods which is home and kitchen appliances. The company is located at 9-1 1st floor, DinastiSentral, 7A, Jalan Kuchai Maju 18, Kuchai Entrepreneurs Park, 58200, Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur. The location of the company is a very strategic location since Kuala Lumpur is the place where many people go shopping. The company business hours are available from Monday to Saturday from 8 a.m. and 8 p.m. and during holiday seasons such as Hari Raya, it is closed. Customers can buy the products directly through our website or can walk in to our stores.